JSE 32:3 Fall 2018 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2018)
In my Editorial in the last issue, I dealt at some length with the topic of experimental replicability, revisiting a subject I’d addressed in another Editorial five years earlier. And back then, I followed that initial Editorial with another, dealing with an important and too often neglected side-issue—namely, whether (or to what extent) we should consider scientific expertise to be an art, or something more like a gift than a skill. As far as I can tell, this interesting topic continues to receive even less attention than the usual concerns over replicability. So now I’d like once again to raise the relevant issues. Perhaps the second time is a charm. Philosopher Karl Popper notoriously once wrote: “Any empirical scientific statement can be presented (by describing experimental arrangement, etc.) in such a way that anyone who has learned the relevant techniques can test it” (Popper 1959/2002:99, emphasis added). In my Editorial last issue, I noted that given the inevitable differences between original experiments and replication attempts—magnified in the behavioral sciences (and parapsychology) by many additional kinds of potentially relevant variables (such as well-documented experimenter effects), it may be unreasonable to expect success when replication attempts are conducted by someone other than the original experimenter. That point is relatively familiar. What I want to consider more closely now are the less familiar, related questions: What are the relevant techniques? Can they be captured and conveyed by a mere list of procedures, like a recipe for baking bread? And in particular: To what extent can these techniques even be learned?